An Economic Analysts of Malaysian Cocoa Prices: A Structural Approach - Rosdi, Mat Lani (1991)

(untitled)
Cocoa industry is vulnerable to price fluctuations arising from fundamental changes in supply and demand and other technical and social factors. Consequently, price variability can affect the producers' returns and the foreign exchange earnings. This study is undertaken to investigate the main factors that determine cocoa prices. Econometric cocoa models for the world and Malaysian markets were developed and estimated using annual time series data. Each model consists of supply, demand and price equations, with stock as the identity. The analyses and standard tests show that the models are satisfactory. The R2 obtained for all the equations are above 0.75 and most coefficients have the correct signs. The RMS%E's are all below 5 percent except for the world price equation and Theil's inequality coefficients are all below 0.005. Our result s show that domestic cocoa prices are determined by prices prevailing in the world market. Domestic stock change is not significant. In the world market itself, stock and consumption are the main factors that influence the behaviour of cocoa prices. World consumption and export demand are significantly influenced by the production index of the industrial nations and price of cocoa. On the supply side, cocoa production is determined by cocoa price lagged by the gestation period. This implies that investment decision on cocoa three to five years earlier is an important factor that determines cocoa supply. The effects of market fundamentals on cocoa prices are further enhanced by the low price elasticities of supply and demand. The effects are therefore substantial. Owing to the importance of cocoa to the economies of producing countries, it is therefore important to ensure cocoa price stability, which may be achieved by efficient price stabilization programmes. Such a programme can be established through improvements of the existing' buffer stock programme of the International Cocoa Agreement, such as, for example, through proper stock management. Promotion and down stream activities are alternative instruments that can be exploited to encourage demand, hence bolster cocoa price. Malaysia should therefore support any programme that aims at stabilizing the world cocoa price.